Design and experiment of the soil-covering and soil-compacting device for seedling raising and sowing of trough type panax notoginseng - Yang, Wencai; Pu, Wang; Xu, Lulu; Tian, Ziyuan; Zhao, Jing; Zhang, Yijie; Yang, Zhenjie (International Journal of Agricultural and Biological Engineering, 2023)
In order to improve the seedling quality of Panax notoginseng, combined with the special agronomic requirements of Panax notoginseng, a sharp angle roller soil-covering and soil-compacting device integrating the functions of soil-covering and soil-compacting was designed. Based on the theoretical analysis of seed ditch conditions, soil-covering process and soil-compacting process, the structure of soil-covering and soil-compacting device was designed. Through theoretical analysis and calculation, the diameter and length of soil-covering and soil-compacting wheel were 20 cm and 10.7-14.1 cm, respectively, the sharp angle and height range were 45°-105° and 0.8-1.6 cm respectively, and the spring stiffness was 38.54 N/mm; Using the discrete element method to simulate the soil-covering and soil-compacting process, it was obtained that when the sharp angle range was 60°-90°, the sharp angle height range was 0.8-1.2 cm, and the soil-covering effect was better; Taking the forward speed, ballast pressure, sharp angle and sharp angle height of the planter as the test factors, and taking the soil-covering thickness, grain spacing and soil compactness as the indexes, the four factor and three-level Box-Behnken Design test was carried out. The response surface test analysis method was used to establish the regression equation between the factors and indexes, and determine the best parameter combination: the forward speed was 6.5 m/min, the ballast pressure was 360.5 N, the sharp angle was 67°, and the sharp angle height was 1 cm, at this time, the soil-covering thickness was 0.64 cm, the grain spacing was 5.03 cm, and the soil compactness was 321.77 kPa. According to the soil trough test, the design of soil-covering and soil-compacting device met the agronomic requirements of plant spacing, soil-compactness and soil-covering thickness during seedling sowing of Panax notoginseng. The research results can provide a reference for the design of Panax notoginseng seedling planter integrating pressing hole (ditching), sowing, soil-covering and soil-compacting. Key words: Panax notoginseng, trough type, seedling raising and sowing, soil-covering and soil-compacting, EDEM, test DOI: 10.25165/j.ijabe.20231605.7606 Citation: Yang W C, Pu W, Xu L L, Tian Z Y, Zhao J, Zhang Y J, et al. Design and experiment of the soil-covering and soil-compacting device for seedling raising and sowing of trough type panax notoginseng. Int J Agric & Biol Eng, 2023; 16(5): 113–122.